Sound Coding in the Auditory Nerve: From Single Fiber Activity to Cochlear Mass Potentials in Gerbils. (21st May 2019) - Huet, A.; Batrel, C.; Wang, J.; Desmadryl, G.; Nouvian, R.; Puel, J.L.; Bourien, J.
Highlights: Functional properties of ANFs were examined in quiet and noisy backgrounds. In low-frequency range, high-SR fibers use temporal coding to encode tone in noise. In high-frequency range, low-SR fibers encode tone-in-noise using rate coding. Low-SR fibers are not detectable using the CAP of the auditory nerve. Round-window mass potentials enable assessment of low-SR fibers. Abstract: Auditory nerve fibers (ANFs) convey acoustic information from the sensory cells to the brainstem using an elaborated neural code based on both spike timing and rate. As the stimulus tone frequency increases, time coding fades and ceases, resulting in high-frequency tone encoding that relies mostly on the spike discharge rate. Here, we recapitulated our recent single-unit data from gerbil's auditory nerve to highlight the most relevant mode of coding (spike timing versus spike rate) in tone-in-noise. We report that high-spontaneous rate (SR) fibers driven by low-frequency tones in noise are able to phase lock ∼30 dB below the level that evoked a significant elevation of the discharge rate, whereas medium- and low-SR fibers switch their preferential mode of coding from rate coding in quiet, to time coding in noise. For high-frequency tone, the low-threshold/high-SR fibers reach their maximum discharge rate in noise and do not respond to tones, whereas medium- and low-SR fibers are still able to respond to tones making them more resistant to background noise. Based on these findings, we first discuss the ecological function of the ANF distribution according to their spontaneous discharge rate. Then, we point out the poor synchronization of the low-SR ANFs, accounting for the discrepancy between ANF number and the amplitude of the compound action potential of the of the auditory nerve. Finally, we proposed a new diagnostic tool to assess low-SR fibers, which does not rely on the onset response of the ANFs.